A radioactive silica-coated gold nanoparticle and a method for producing thereof - Hussain, Siti Aslina; Mohd Yunos, Mohd Amirul Syafiq (2014)
The present invention relates to a radioactive tracer characterized by a silica-coated gold nanoparticle comprising 0.1 to 1 wt% gold, having a diameter in a range of 70 to 200 nanometers and radioactivity in a range of 55.5 to 129.5 MBq. The present invention also provides a method for producing a radioactive tracer comprising a silica-coated gold nanoparticle, characterized by the steps of heating the colloidal gold nanoparticle solution; mixing the colloidal nanoparticle solution with an alcohol to form a mixture; adding an ammonia solution, followed by a silica compound into the mixture to form the silica-coated gold nanoparticle; washing and centrifuging the silica-coated gold nanoparticle, thereby separating the silica-coated gold nanoparticle from unwanted solution; calcining the silica-coated gold nanoparticle for producing silica-coated gold nanoparticle powder; subjecting the silica-coated gold nanoparticle powder to neutron irradiation.